2002
DOI: 10.1068/p3252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geometric Distortions on Face-Recognition Performance

Abstract: The importance of ‘configural’ processing for face recognition is now well established, but it remains unclear precisely what it entails. Through four experiments we attempted to clarify the nature of configural processing by investigating the effects of various affine transformations on the recognition of familiar faces. Experiment 1 showed that recognition was markedly impaired by inversion of faces, somewhat impaired by shearing or horizontally stretching them, but unaffected by vertical stretching of faces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
133
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 46 publications
22
133
9
Order By: Relevance
“…This is consistent with previous research demonstrating that geometric distortions, such as stretching, do not impair recognition accuracy (Hole et al, 2002;Sandford et al, 2013). These previous studies used famous/nonfamous judgment tasks.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with previous research demonstrating that geometric distortions, such as stretching, do not impair recognition accuracy (Hole et al, 2002;Sandford et al, 2013). These previous studies used famous/nonfamous judgment tasks.…”
Section: Discussionsupporting
confidence: 81%
“…Hole et al, 2002). However face recognition is impaired by other transformations, such as non-global face distortions (Hole et al, 2002), photographic negation (Galper, 1970) and inversion (Yin, 1970), and also by changes in pose and expression. Future research could investigate how these transformations affect the set averaging process.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to photographs, by doubling the height, Hole, George, Eaves and Rasek (2002) found that recognition accuracy of familiar (celebrity) faces did not decrease relative to unaltered images (although reaction times were slower in one of their four experiments). However, as described in Astbury (2011), doubling height or width of familiar-face (celebrity) composites substantially improved an observer's ability to correctly name the face.…”
Section: Facilitating Recognition (Naming) Of Compositesmentioning
confidence: 92%
“…Relative to looking at the face front-on, this 'perceptual' stretch about doubled correct naming, from 17% to 36%. Hole et al (2002) argued that, for photographs of faces, an observer's cognitive system may be normalizing a stretched face prior to recognition, to fit with how a face usually appears, or that the memory itself may be altered to accommodate the transformation, a 'deformable template' theory. More-recent research by the first author (unpublished) has found that the null effect of stretching extends to unfamiliar-face recognition, which argues for the former case: normalisation of an incoming face not deformation of memory.…”
Section: Facilitating Recognition (Naming) Of Compositesmentioning
confidence: 99%
“…Furthermore, some studies of human face recognition have shown it to be highly tolerant of certain manipulations of the shape. For example, Hole, George, Eaves & Rasek (2002) demonstrated that familiar face recognition was completely unaffected by distorting the aspect ratio of photographs by up to 2:1, vertical to horizontal. On the other hand, research on the caricature effect suggests that manipulations of shape which emphasise idiosyncratic characteristics can improve identification (e.g., Rhodes, 1996).…”
Section: Average Shapes and Average Texturesmentioning
confidence: 99%